Critical Thinking Skill Enhancement Through Phenomenon - Based Learning in an English Classroom - Jaengsaengthong, Wipasiri; Inlop, Hathaichanok; Kuptanaroaj, Nattapon; Moosikajaroen, Wiparat (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
Critical thinking skill is an important skill that learners should definitely be enhanced in, particularly in English classrooms since English teaching and learning activities are associated with interpersonal language communication, including exchanging ideas and opinions, discussing and expressing points of view or perspectives through English communication. Somehow, critical thinking skill cannot be naturally developed. The learners must be appropriately enhanced and obtain the opportunity to practice sufficiently. Currently, one of the approaches in the spotlight based on constructivism theory is Phenomenon-Based Learning, which is an interdisciplinary learning process via active learning that stimulates learners from cooperatively observing phenomenon with holistic points of view, questioning, determining problems relevant to the studying phenomenon, practical learning to find out the answers via inquiry-based learning from various learning sources ; and examining learners’ understanding through a variety of learners’ presentations based on their aptitudes and interests. In each procedure of enhancing the critical thinking skill of the learners, there are interpretation, analysis, inference, assessment, explanation, and self-regulation along with developing speaking, listening, reading, and writing English skills through practice.